The Effect of Organizational Culture on Employee Performance with Job Satisfaction as an Intervening Variable at the Head Office of PT. Permodalan Nasional Madani Jakarta - Fakmal Ali (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of organizational culture on employee performance with job satisfaction as an intervening variable. This study uses a quantitative approach. The population used in this study are all employees of the Head office of PT. Permodalan Nasional Madani Jakarta, totaling 1,552 people by taking a research sample of 200 employees. The data collection technique was carried out using a questionnaire through online. The analysis technique used is Structural Equition Modeling – Partial Least Square (SEM-PLS) with the SmartPLS 3.0 tool. The results showed that there was a positive and significant direct effect: organizational culture on job satisfaction, job satisfaction on performance, and organizational culture on performance. Also the indirect influence of organizational culture on performance through job satisfaction. The conclusion is that there is an influence of job satisfaction in mediating the influence of organizational culture on employee performance at the Head office of PT. Permodalan Nasional Madani Jakarta